Kejahatan Teknologi Informasi (Cyber Crime) dan Penanggulangannya dalam Hukum Indonesia - Ferdinan Sitompul; Alfren Petrus Putra Manik; Carlos Daniel Sinaga; Angel Theresia Purba; Andy Satria (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This journal examines the phenomenon of Information Technology crimes, commonly known as cybercrime, and the legal countermeasures in the context of Indonesian law. The continuous advancement of information technology has opened doors for criminals to exploit digital means as tools to achieve their illicit objectives. This research aims to analyze the most prevalent types of information technology crimes in Indonesia and identify the legal framework's role in combating and mitigating the negative impacts of these crimes. The research methodology involves the analysis of secondary data, including case studies of information technology crimes that have occurred in Indonesia. The findings indicate that crimes such as identity theft, online fraud, and ransomware attacks pose serious threats to digital security in Indonesia. Therefore, concerted efforts are needed to develop an effective legal framework to combat these crimes. The journal also reviews the development of legal regulations concerning information technology crimes in Indonesia, such as the ITE Law (Electronic Information and Transactions Law), and analyzes the effectiveness and challenges faced in law enforcement. Additionally, the research discusses preventive and counteraction initiatives undertaken by the government, law enforcement agencies, and the private sector. The research findings provide in-depth insights into the complexity of information technology crime issues and the challenges in addressing them in Indonesia. The implications of this research are expected to support the improvement of policies, regulations, and more effective law enforcement efforts in facing the threats of information technology crimes in the future.